La presencia portuguesa en Revista de las Españas (1926-1936) - Antonio Sáez Delgado (Catalonia)
Revista de las Españas (1926-1936), published in Madrid by the Ibero-American Union, has so far been almost disregarded in the field of literary and cultural relations between Portugal and Spain. However, the presence of Portuguese collaborators is notable, and its projection runs parallel to that of La Gaceta Literaria, with which it shares Ibero-American ideals. In this context, the presence of the writer Ernesto Giménez Caballero is fundamental in both projects, since in addition to directing La Gaceta Literaria he coordinated the section «Revista Literaria Ibérica» in Revista de las Españas. The importance of the Portuguese presence in Revista de las Españas is shown by the publication of four hitherto unknown drawings by José de Almada Negreiros, as well as numerous articles on Portuguese literature by authors such as Fidelino de Figueiredo or Augusto d’Esaguy. However, Giménez Caballero’s ideological drift towards fascism ended up disrupting the Iberian interactions generated in the two journals, as he tried to locate the heartland of Iberian cultures in Madrid.